If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 15 = 6x + 13 Reorder the terms: 15 + 10x = 6x + 13 Reorder the terms: 15 + 10x = 13 + 6x Solving 15 + 10x = 13 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 15 + 10x + -6x = 13 + 6x + -6x Combine like terms: 10x + -6x = 4x 15 + 4x = 13 + 6x + -6x Combine like terms: 6x + -6x = 0 15 + 4x = 13 + 0 15 + 4x = 13 Add '-15' to each side of the equation. 15 + -15 + 4x = 13 + -15 Combine like terms: 15 + -15 = 0 0 + 4x = 13 + -15 4x = 13 + -15 Combine like terms: 13 + -15 = -2 4x = -2 Divide each side by '4'. x = -0.5 Simplifying x = -0.5
| 20x-3*5x=22 | | 4x+3=2(2x-5) | | -2+2n-6=-6 | | y+14-3y=0 | | 3x-y+50=180 | | -1x+2=-2x+-1x | | 2(3x-5)=-29 | | 6v^3+12v^2-48v=0 | | 8.95+0.10x=0+0.06x | | -y+6-3y=y+2 | | 2x-5=-x+13 | | -17+62=-5(x+4) | | -8(-8x)-6=-22 | | -3(8-4p)=-15+3p | | 2n+4+6=18 | | x-2(x+1)=3x-10 | | -0.6(r+2)=1.8 | | 110+6x=119+5x | | 2x^2-2x+1=16 | | 5(3x-4)=7+2x | | -15x+9y=0 | | 3(0)=2x+3 | | 6(5x-4)+9=-2(2x+8)-30x | | 7-3x^2=0 | | 720-45x=180 | | -2x+6+5=11 | | -6(x+5)=-30+x | | 0=1+6x+y | | x-(.35x)=375000 | | 3x-4y=93 | | 5r(2)-5=562 | | 180+45x=-720 |